2018
DOI: 10.1016/j.jsr.2018.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Talking with teens about traffic safety: Initial feasibility, acceptability, and efficacy of a parent-targeted intervention for primary care settings

Abstract: The results from this pilot study provide support for implementation fidelity and establish a proof-of-concept for the Talking with Teens about Traffic Safety Program. The results provide guidance for developing partnerships with pediatricians and parents to develop parent-teen communication interventions on injury prevention topics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
2
10
0
Order By: Relevance
“…Reviews of parenting interventions outside of clinic settings have shown favorable associations with the quality of parent-adolescent relationships, as well as health-related outcomes . Emerging literature shows that clinic-based interventions can effectively improve parenting communication and relationships as well as parent-adolescent communication about specific adolescent health-related outcomes in domains of sexual health, alcohol use, and teen driving . Our study supports the groundwork for a renewed interest in interventions and strategies designed to nurture and support the development of high-quality parent-adolescent relationships, above and beyond efforts targeting early childhood .…”
Section: Discussionsupporting
confidence: 65%
“…Reviews of parenting interventions outside of clinic settings have shown favorable associations with the quality of parent-adolescent relationships, as well as health-related outcomes . Emerging literature shows that clinic-based interventions can effectively improve parenting communication and relationships as well as parent-adolescent communication about specific adolescent health-related outcomes in domains of sexual health, alcohol use, and teen driving . Our study supports the groundwork for a renewed interest in interventions and strategies designed to nurture and support the development of high-quality parent-adolescent relationships, above and beyond efforts targeting early childhood .…”
Section: Discussionsupporting
confidence: 65%
“…Surveys were administered through CHOP's Research Electronic Data Capture (REDCap) portal and designed to be completed in ≤ 10 min (Harris et al, 2009(Harris et al, , 2019. The survey was informed by young driver research (Anderson et al, 2018;Mirman et al, 2018aMirman et al, , 2018bTaylor & Henninger, 2015). First, providers answered questions about their practice location, clinical role, and demographic information.…”
Section: Methodsmentioning
confidence: 99%
“…Health and behavioral service providers may be uniquely poised to provide resources or counsel and assist families as they make transportation-related decisions. Several studies have reported parents, adolescents, and providers themselves consider the teen's primary care physician a resource for information about transportation topics, and in particular, independent driving (Ford et al, 2016;Gaw et al, 2020;Mirman et al, 2018aMirman et al, , 2018b. However, a recent survey found only 62% of primary care physicians were comfortable counseling their patients on driving (Gaw et al, 2020).…”
mentioning
confidence: 99%
“…Mclaughlin et al (2019) signi cantly improved children's pedestrian crossing behaviour through interactive pedestrian safety education. Mirman et al (2018) found that teenagers could improve their tra c safety awareness through discussions with their parents.…”
Section: Street-crossing Risk Perceptionmentioning
confidence: 99%